ANALISIS KELAYAKAN FINANSIAL USAHATANI SALAK PONDOH DI DESA WONOHARJO, KECAMATAN SUMBEREJO, KABUPATEN TANGGAMUS - Muhammad Azmi; Wan Abbas Zakaria; Ktut Murniati (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2017)
The research aims to analyze: financial feasibility and sensitivity of salak pondoh farming.  This research was conducted at Wonoharjo, Sumberejo, Tanggamus. The data was collected in Januari 2016.  The samples  were 44 Salak farmers who were selected by using  simple random sampling method.  The analysis methods of this research were financial feasibility analysis and sensitivity analysis.  The results showed that based of Net B/C, Gross B/C, Payback Periode (PP), NPV, IRR, and sensitivity, salak pondoh farming was profitable financially and feasibly to be developed.  The Net B/C and Gross B/C values were bigger than 1, the value of NPV was bigger than 0, and IRR value of salak pondoh farming was greater than 12 percent (the used interest rate).  The PP analysis for salak pondoh farming system showed that the initial cash out flow of investment could be recovered in  less than 25 years.  Based on the changes of sensitivity analysis, the increase of production cost was 5.90%, but the decreaes of production price and production quantity were 10 percent and 30 percent.  The result of sensitivity analysis showed that salak pondoh farming was sensitive to changes, but wat still profitable and feasible to be continued.Key words : feasibility, financial, salak pondoh, Tanggamus Regency